2019
DOI: 10.1371/journal.pone.0226993
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative engineering study of ecosystem robustness using thermodynamic power cycles as case studies

Abstract: Human networks and engineered systems are traditionally designed to maximize efficiency. Ecosystems on the other hand, achieve long-term robustness and sustainability by maintaining a unique balance between pathway efficiency and redundancy, measured in terms of the number of flow pathways available for a given unit of flow at any node in the network. Translating this flow-based ecosystem robustness into an engineering context supports the creation of new robust and sustainable design guidelines for engineered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Their analysis, from ENA metrics has shed light on virtual water interactions in the global agriculture and livestock trading system (Yang et al, 2012). The study by Fang and Chen (2015) has shown that the VWMN of the Heihe river basin is highly redundant, counterintuitively that human-designed networks should be more efficient (Goerner et al, 2009;Kharrazi et al, 2013;Panyam & Layton, 2019;Ulanowicz et al, 2009). Zhang et al (2019) compare the VWMN of Guangdong with the consumption of water resources per unit of GDP, to find the sectors with the least connection to the network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their analysis, from ENA metrics has shed light on virtual water interactions in the global agriculture and livestock trading system (Yang et al, 2012). The study by Fang and Chen (2015) has shown that the VWMN of the Heihe river basin is highly redundant, counterintuitively that human-designed networks should be more efficient (Goerner et al, 2009;Kharrazi et al, 2013;Panyam & Layton, 2019;Ulanowicz et al, 2009). Zhang et al (2019) compare the VWMN of Guangdong with the consumption of water resources per unit of GDP, to find the sectors with the least connection to the network.…”
Section: Introductionmentioning
confidence: 99%
“…The application of ENA metrics to assess ecosystems, along with ecosystem characteristic values, on urban metabolism analysis will provide unique design information for urban metabolic processes to mimic nature's sustainability (Panyam & Layton, 2019). One property that has been observed is that ecosystems present a balanced configuration between resource efficiency and functional redundancy (Fath, 2015; Ulanowicz, 1986), which is believed to lead to robust and sustainable outcomes.…”
Section: Introductionmentioning
confidence: 99%